What is known about the germination of herbaceous-shrub species from open wetlands in the Cerrado? - Santos, Lauana Vieira dos (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Biológicas, Programa de Pós-Graduação em Ecologia, 2024.